Answer:
The given expression is factored into [tex](2k+3)(4k^2-6k+9)[/tex]
Step-by-step explanation:
Given:
The expression to factor is given as:
[tex]8k^3+27[/tex]
We observe that 8 = [tex]2\times 2\times 2=2^3[/tex]
Also, [tex]27 = 3\times 3\times 3=3^3[/tex]
So, the above expression can be rewritten as:
[tex](2k)^3+3^3[/tex]
The above expression is of the form [tex]a^3+b^3[/tex].
We know that the above identity is factored as:
[tex]a^3+b^3=(a+b)(a^2-ab+b^2)[/tex]
Here, [tex]a=2k\ and\ b=3[/tex]
Therefore, the given expression can be factored using the above identity and is factored as:
[tex](2k)^3+3^3=(2k+3)((2k)^2-(2k)(3)+3^2)\\\\(2k)^3+3^3=(2k+3)(4k^2-6k+9)[/tex]
Hence, the given expression is factored into [tex](2k+3)(4k^2-6k+9)[/tex]